Indústria cultural e forró eletrônico no Rio Grande do Norte - Costa, Jean Henrique (2012)
The present study aimed to understand how and to what extent the electronic forró, currently hegemonic in the music market in the state of Rio Grande do Norte, establishes and maintains relations of domination in the social contexts in which it is produced, transmitted and received. Based, in significant form-content, on the writings of the first generation of theorists of the so-called Frankfurt School (Critical Theory), particularly with Theodor W. Adorno, and systematically using the contributions of the Cultural Studies (from the Centre for Contemporary Cultural Studies of Birmingham) and of the sociology of Pierre Bourdieu, this study aimed to perform, in the fertile intersection of these references, a critical possibility of interpretation of the electronic forró predominantly spread in the state of Rio Grande do Norte. To this end, aiming at a better apprehension of the so-called capital circuits/culture circuits , this study resulted from a qualitative investment of research, based on structured interviews with musicians, entrepreneurs of the sector and music consumers, as well as on the analysis of the themes contained in the official discography of the electronic forró band called Garota Safada (Shameless Girl). As a general empirical conclusion, it was possible to infer that far from the significant presence of domination or mere prevalence of oppositions, there is a relational pluralism of forms of domination and ways of resistances present in the production and consumption of electronic forró, regardless of gender, age, income, education or place of residence. However, the artifices of the cultural industry has been shown to be efficient: from large-scale businessmen to small producers enabled by the so-called open markets . The currentness of the concept of cultural industry is based on the idea that its products are offered systematically (the systematic insistence of everything to everyone) and on the notion that its production primarily meets the administrative criteria of control over the effects on the receiver (capacity of prescription of desires). Thus, the Adornian reflection on the pseudo-individualization leads to the inference that even in some of the most apparent ways of negotiation and/or refusal regarding the consumption of forró, certain behaviors of the cultural industry still prevail both in the very (re)interpretation of the forró and in the choice of other music genres also standardized, rationalized and massified. Therefore, despite the absence of cause-effect relation and the recognition of the popular capacity of re-elaboration and contestation of the media consumption, some world views prevailing in relation to the electronic forró establish or, at least, support some hegemonic ideologies, especially those concerning the life style, consumption and genre relations (fun by all means). Therefore, due the massification of certain songs, some ways of dissemination of values, beliefs and feelings are potentially experienced from the electronic forró. So, it is presumable that in the current advance of the process of semiformation (Halbbildung), the habitus of a part of the youth from the state of Rio Grande do Norte reinforces and is reinforced by the centrality of the trinomial fun, love and sex present in the songs, emphasized in some constructive practices of sense and in certain flows of social significance